Photometric diagnostics of plasma of planar capacitive RF discharge in argon at 1 atm pressure - Bazhenov, V.Yu.; Gubarev, S.M.; Tsiolko, V.V.; Levko, D.S. (Вопросы атомной науки и техники, 2018)
The results of study of the plasma parameters of radio frequency capacitive discharge with isolated electrodes in atmospheric-pressure argon by means of bremsstrahlung photometry in wavelength range 400…600 nm are presented. Time-averaged spatial distributions of the plasma electron temperature are experimentally obtained for low-current α-and high-current γ-modes of the discharge glow. The comparison of the experimental results with the preliminary data of the discharge computer modeling by a particle-in-cell method is presented.